2021
DOI: 10.1101/2021.09.16.460722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive processing of a common stimulus synchronizes brains, hearts, and eyes

Abstract: Neural, physiological and behavioral signals synchronize between human subjects in a variety of settings. Multiple hypotheses have been proposed to explain this interpersonal synchrony, but there is no clarity under which conditions it arises, for which signals, or whether there is a common underlying mechanism. We hypothesized that similar cognitive processing of a shared stimulus is the source of interpersonal synchrony, measured here as inter-subject correlation. To test this we presented informative videos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 99 publications
(211 reference statements)
1
1
0
Order By: Relevance
“…Applying the clustering algorithms to physiological synchrony in EDA or heart rate resulted in lower classification accuracies than in EEG, and generally led to performance near theoretical chance level. This is in line with other work, where synchronous changes in peripheral modalities have been shown to reflect attentional engagement with narrative stimuli less robustly than EEG (Ki et al, 2016;Perez et al, 2020;Stuldreher et al, 2020a;Madsen and Parra, 2021).…”
Section: Clustering Performance Using Physiological Synchrony In Either Eeg Eda or Heart Ratesupporting
confidence: 92%
See 1 more Smart Citation
“…Applying the clustering algorithms to physiological synchrony in EDA or heart rate resulted in lower classification accuracies than in EEG, and generally led to performance near theoretical chance level. This is in line with other work, where synchronous changes in peripheral modalities have been shown to reflect attentional engagement with narrative stimuli less robustly than EEG (Ki et al, 2016;Perez et al, 2020;Stuldreher et al, 2020a;Madsen and Parra, 2021).…”
Section: Clustering Performance Using Physiological Synchrony In Either Eeg Eda or Heart Ratesupporting
confidence: 92%
“…It may be so that combining multiple modalities compensates for potential noisy observations in any of the modalities. Recent work of Madsen and Parra ( 2021 ) showed that physiological synchrony in EEG and heart rate in response to instructional videos are co-modulated. Thus, one noisy measurement may be compensated for by another measurement.…”
Section: Discussionmentioning
confidence: 99%